Maciej Dercz, Konstytucyjne prawo dziecka do szczególnej opieki zdrowotnej, seria Monografie LEX, Wolters Kluwer SA, Warszawa 2016 (opr. Paulina Jankowska) - Jankowska, Paulina (Studia Prawa Publicznego, 2019)
Maciej Dercz, Konstytucyjne prawo dziecka do szczególnej opieki zdrowotnej, seria Monografie LEX, Wolters Kluwer SA, Warszawa 2016 (opr. Paulina Jankowska)